Heart rate variability between elite archers and sedentary adults - Huang, M.W.; Lin, G.; Fan, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Heart rate variability (HRV) measured by power spectral analysis has been used as a reliable, reproducible, and non-invasive technique for assessing the function of the autonomic nervous system during exercise. Archery is described as a fine and static sport which requires good concentration and proper strength during the drawing, aiming and release phases The purpose of this study was to determine whether differences in HRV existed between elite archers (EA) and sedentary adults (SA) in the supine and standing position.